India's and China's recent experience with reform and growth/edited by Wanda Tseng - "Tseng, Wanda (ed.)" (New York, 2005)
China and India already rank among the world's largest economies, and each is moving rapidly towards the centre stage of the global economy. In this process different priorities have been placed on economic reforms in the past two decades - China taking a more outward strategy and India, until recently, a more inward one. Can they continue to rank among the fastest expanding economies? This volumes addresses the issue, highlighting what has worked and what more needs to be done to ensure sustained rapid economic growth and poverty reduction. Addressing the two countries' recent experiences with growth and reform, this book provides important insight for other developing economies.
Keywords: India-Economic policy